THE APPLICATION OF INTERACTIVE PLATFORM «TEACH. TIME» IN THE PROCESS OF LEARNING PRIMARY SCHOOL CHILDREN - Nechiporenko, Kateryna P.; Sizonenko, Kateryna V. (Educological discourse, 2016)
In this article the authors investigated the learning process of children in primary school. Theoretical analysis of the research literature on the subject has shown that the problem of formation of fully developed personality pupils of primary school is relevant and needs constantly search to improve the educational process in primary school. In this regard, it was identified the peculiarities of interactive learning technology, was presented an interactive platform «Teach. Time», its essence and opportunities in the formation of fully developed personality of primary schoolchildren in the educational and creative activities in primary school.